China: Twenty Years of Economic Reform - Garnaut, Ross (ANU Press, 2012)
China: Twenty Years of Reform outlines the experiences of China over the past two decades. It highlights the processes of reform, successes achieved, and problems faced during the economic transition. "China, and its relations with the international community, have been transformed. China's economy has expanded five times, and its foreign trade by twelve. It has greatly increased consumption levels of what had been about half of the world's people in poverty." - Ross Garnaut "Tremendous progress has been made over the past twenty years, but much more needs to be done in setting up a more open, efficient and transparent trade system, in line with the requirements of the WTO." - Ligang Song "Radical reform is neither in China's tradition, nor is it an easy task. Given the difficulties of the reform task and the structure of the political economy, it will probably take a few more years for China to accomplish SOE reform and reforms in other areas." - Yiping Huang "The most remarkable aspect of China's agricultural reform was it's "spillover" effect. Non-agricultural activities in rural China sprang up immediately after the reforms began-the gross output value of TVEs grew at 24 per cent per annum from 1978 to 1995 and employment grew at 9 per cent per annum." - Yongzheng Yang